2012
DOI: 10.3390/ijms130911247
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Guided Isolation of the Cytotoxic Terpenoids from the Roots of Euphorbia kansui against Human Normal Cell Lines L-O2 and GES-1

Abstract: The dried roots of Euphorbia kansui (kansui) have been used for centuries in China as a herbal medicine for edema, ascites, and asthma. The 95% ethanol extract showed a significant inhibition of cell proliferation against human normal cell lines L-O2 and GES-1. Bioassay-guided separation of the 95% ethanol extract from the roots of E. kansui led to the isolation of 12 diverse terpenoids whose structures were identified by 1H, 13C NMR spectroscopy and ESI-MS as kansuinine A (1), kansuinine B (2), kansuinine C (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…NMR as well as mass spectrometry data of the isolated euphol correlated with previous literature reports (Lin et al, 2000;Zhang et al, 2012).…”
Section: Soil and Plant Extractionsupporting
confidence: 87%
See 1 more Smart Citation
“…NMR as well as mass spectrometry data of the isolated euphol correlated with previous literature reports (Lin et al, 2000;Zhang et al, 2012).…”
Section: Soil and Plant Extractionsupporting
confidence: 87%
“…Lin et al, 2000;Zhang et al, 2012).2.4. Comparison of historical and recent satellite imagesGoogle earth satellite images of the collection site were obtained from the internet (accessed 2014-03-20) and visually compared for the remains of plants and the possible formation of new fairy circles from satellite images of2003, 2004, 2010, 2012 and 2013.…”
mentioning
confidence: 97%
“…Different pharmacological activities of C. odorata leaf extract might be due to the combined action of these phenolic compounds. In a previous study, 3‐ O ‐benzoyl‐20‐deoxyingenol from Euphorbia kansui roots showed significant inhibition of cell proliferation against human normal cell lines .…”
Section: Resultsmentioning
confidence: 91%
“…The result was in accordance with previous reports concerning the cytotoxic activity of euphol (1). [ 9 17 18 19 20 21 ] It is worthy to mention that euphol (1) was the only major compound found in the milky sap of leaves as detected by thin layer chromatography, while α-glutinol (2) and stigmasterol (3) were absent. This is the first report on the chemical investigation of E. ammak growing in Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%